Syncope Linked to QT‐Interval Prolongation and Global T‐Wave Inversion: A Clinical Case of Acute Pulmonary Embolism - Xue‐Yan Zhang; Jing‐Xiu Li; Min Gao; Xue‐Qi Li; Ming‐Yu Zhang (Annals of Noninvasive Electrocardiology)
ABSTRACT The incidence and mortality rates of acute pulmonary embolism (APE) are high in clinical emergencies, making early diagnosis and risk stratification crucial. Electrocardiogram (ECG) plays a significant role in guiding the diagnosis and differential diagnosis of pulmonary embolism. Acute pulmonary embolism can present with various ECG manifestations. The presence of pulmonary hypertension and increased right ventricular load in pulmonary embolism can lead to T wave inversion in the right cardiac lead. Additionally, some patients may exhibit a prolonged QT interval, which is associated with the pathophysiological processes resulting from both pulmonary hypertension and myocardial ischemia.